Effect of microbial interaction on the colonization rate of Actinomyces viscosus or Streptococcus mutans in the dental plaque of rats. - Beckers, H J (1982)
The resident oral microflora of conventional Osborne-Mendel rats was challenged with Actinomyces viscosus or Streptococcus mutans strains. The adherence of the inoculated organism to the tooth surface and the subsequent growth were studied by means of viable counts determination. The initial growth rate of S. mutans in conventional rats was lower than in mono-associated gnotobiotic rats (doubling time, td = 5 h versus td = 1.1 h). The delayed start of growth and the low initial growth rate indicated that a competitive interaction between S. mutans and the resident microflora occurred. The initial growth rate of A. viscosus in conventional rats (td = 3.1 h) was approximately the same as that in gnotobiotic rats (td = 2.8 h). The start of growth of A. viscosus was only slightly delayed compared with the start in gnotobiotic rats. These results suggest a neutralistic relationship between A. viscosus and the resident microflora. A. viscosus reached a stationary level about 7 days after inoculation, whereas the S. mutans strains did not reach stationary levels until 2 weeks after inoculation.